Overview of the recent US legislative initiatives for the Arctic development - Alexander L. Voronenko (Арктика и Север, 2019)
In conditions of a significant increase in the world community’s attention to the Arctic, as well as intensive development of technologies for its study and development, the low activity of the USA in this area is noteworthy. The article is devoted to a review of some aspects of the US home policy in the Arctic. It also contains an analysis of two bills submitted to the US Congress aimed at increasing the economic presence in the Arctic region. The author notes the increasing scientific and practical interest of the Alaska po-litical elites in the study and development of the Arctic.